Neural correlates of psychodynamic and non-psychodynamic therapies in different clinical populations through fMRI: A meta-analysis and systematic review - Cera, Nicoletta; Monteiro, Jessica; Esposito, Roberto; Di Francesco, Giulia; Cordes, Dietmar; Caldwell, Jessica Z. K.; Cieri, Filippo (Frontiers in Human Neuroscience, 2022)
Background: The COVID-19 pandemic has exacerbated the ongoing crisis in psychiatric and psychological care, contributing to what we have identified as a new psychological and psychiatric pandemic. Psychotherapy is an effective method for easing the psychological suffering experienced also by the various impacts of COVID-19. This treatment can be examined from a neurological perspective, through the application of brain imaging techniques. Specifically, the meta-analysis of imaging studies can aid in expanding researchers’ understanding of the many beneficial applications of psychotherapy. Objectives: We examined the functional brain changes accompanying different mental disorders with functional Magnetic Resonance Imaging (fMRI), through a meta-analysis, and systematic review in order to better understand the general neural mechanism involved in psychotherapy and the potential neural difference between psychodynamic and non-psychodynamic approaches. Results: After duplicates removal and assessment of the content of each published study, we included 36 sources. The map including all studies that assessed longitudinal differences in brain activity showed two homogeneous clusters in the left inferior frontal gyrus, and caudally involving the anterior insular cortex (p<0.0001, corr.). Similarly, studies that assessed psychotherapy-related longitudinal changes using emotional or cognitive tasks (TASK map) showed a left-sided homogeneity in the anterior insula (p<0.000) extending to Broca’s area of the inferior frontal gyrus (p<0.0001) and the superior frontal gyrus (p<0.0001). Studies that applied psychodynamic psychotherapy showed Family-Wise Error (FWE) cluster-corrected (p<0.05) homogeneity values in the right superior and inferior frontal gyri, with a small cluster in the putamen. No FWE-corrected homogeneity foci were observed for Mindful- based and cognitive behavioral therapy psychotherapy. In both pre- and post- therapy results, studies showed two bilateral clusters in the dorsal anterior insulae (p=0.00001 and p=0.00003, respectively) and involvement of the medial superior frontal gyrus (p=0.0002).